Multilevel Modular DC/DC Power Converter for High-Voltage DC-Connected Offshore Wind Energy Applications - Parastar, Amir; Kang, Yong Cheol; Seok, Jul-Ki (IEEE transactions on industrial electronics (1982), 2015)
Recently, the interest in offshore wind farms has been significantly increased because of the stronger and more stable winds at sea, which will lead to a higher power production. DC/DC power conversion solutions are becoming more popular for fulfilling the growing challenges in the high-voltage (HV) dc-connected offshore wind power industry. This paper presents several multilevel modular dc/dc conversion systems based on the capacitor-clamped (CC) module concept for high-power offshore wind energy applications. Two types of the CC modules, namely, the double-switch (DS) module and the switchless (SL) module, are discussed. A soft-switching technique is adopted to achieve minimal switching losses and the maximum system efficiency. Theoretical analysis is carried out for the 2n+1-level cascaded configurations based on the CC modules. The inherent interleaving property of the proposed configurations effectively reduces the output voltage ripple without adding extra components. A cascaded hybrid topology is developed by the combination of DS and SL modules. The proposed hybrid topology achieves higher efficiency and lower component count. The cascaded hybrid approach is evaluated in terms of the power device count, reliability, and efficiency against other HV dc/dc topologies to demonstrate its advantage for HVDC-connected offshore wind farms. The experimental results of two 5-kW prototype CC converters are presented to validate the theoretical analysis and principles as well as attest the feasibility of the proposed topologies.